Cell cycle-dependent translocation and regulatory mechanism of CacyBP/SIP in gastric cancer cells. Issue 1 (January 2018) - Chen, Yang; Zhang, Kun; Wang, Xiaosu; Li, Qiaoneng; Wu, Qingfeng; Ning, Xiaoxuan
Abstract : Our previous results showed that calcyclin-binding protein/Siah-1-interacting protein (CacyBP/SIP) inhibits the proliferation and tumorigenicity of gastric cancer; however, the exact mechanism remains unclear, especially from the aspect of cell cycle. The subcellular localization of CacyBP/SIP, Siah-1, and Skp1 in SGC7901 gastric cancer cells was assessed by immunofluorescence after cell cycle synchronization. Levels of CacyBP/SIP, Siah-1, Skp1, β-catenin, and p-ERK1/2 were analyzed by western blotting. CacyBP/SIP phosphorylation (p-CacyBP/SIP) and the combining capacity of Siah-1 and Skp1 with CacyBP/SIP in nucleoprotein were determined by immunoprecipitation. CacyBP/SIP, Siah-1, and Skp1 were mainly in the cytoplasm in the G1 phase, but translocated to the nucleus during G2. Their expression in total protein was not altered, but elevated in the G2 phase in nucleoprotein. The CacyBP/SIP nucleus translocation of cells transfected with mutant CacyBP/SIP that does not bind S100 (CacyBP–ΔS100) was significantly increased compared with wild-type CacyBP/SIP. In the G2 phase, p-CacyBP/SIP expression and the combining capacity of Siah-1 and Skp1 with CacyBP/SIP were all increased, whereas levels of β-catenin and p-ERK1/2 reduced, compared with the G1 phase. CacyBP/SIP or CacyBP–ΔS100 overexpression was correlated with constitutively low β-catenin expression and affected its level through cell cycle. CacyBP/SIP overexpression led to retarded proliferation, G1 arrest, and β-catenin reduction, which could be abolished by lithium chloride, β-catenin activator, and further enhanced by the Wnt inhibitor XAV-939. In addition, CacyBP–ΔS100 further suppressed cell proliferation and induced G1 arrest compared with CacyBP/SIP. In conclusion, CacyBP/SIP nuclear localization, dependent on S100 protein, suppresses gastric cancer tumorigenesis through β-catenin degradation and the dephosphorylation of ERK1/2 during the G2 phase.